Lenalidomide-Associated ITP. (17th July 2011) - Herold, Christina I.; Gasparetto, Cristina; Arepally, Gowthami M.
Abstract : Lenalidomide is a potent immunomodulatory agent being used increasingly for treatment of hematologic malignancies including multiple myeloma and myelodysplasia. The common toxicities of lenalidomide, including dose-limiting myelosuppression, are well described. However, the immunomodulatory properties of lenalidomide may give rise to unexpected autoimmune complications. Herein, we describe a case of immune thrombocytopenic purpura (ITP) associated with use of lenalidomide.